ANALYSIS OF MACROECONOMIC EFFECTS ON THE YIELD OF CORPORATE BONDS IN INDONESIA - Sianturi, Anastasia; Sihombing, Pardomuan (Dinasti International Journal of Management Science, 2020)
This study aims to examine and obtain empirical evidence of the effects of inflation, BI rate, exchange rate, foreign exchange reserves and the oil price to yield corporate bonds in Indonesia. An increase in the number of issuers and corporate bond issuance value in Indonesia means that many companies are using and seek financing through the issuance of bonds. Several studies have been conducted, inconsistencies results of research on factors affecting yield corporate bonds in Indonesia. This study uses a quantitative approach to the type of associative causal research. Measurement of variables in this study using a time series analysis were processed using Eviews program 10. This research was conducted using monthly data within the period of 2015 to 2018. The results of this research that inflation positively affects yield corporate bonds. BI rate has a positive effect on the yield of corporate bonds. Exchange rate positive effect on the yield of corporate bonds. Foreign exchange reserves negatively affect yield corporate bonds. Oil price positive effect on the yield of corporate bonds.